2016
DOI: 10.1007/978-3-662-53354-3_16
|View full text |Cite
|
Sign up to set email alerts
|

Stable Matching with Uncertain Linear Preferences

Abstract: Abstract. We consider the two-sided stable matching setting in which there may be uncertainty about the agents' preferences due to limited information or communication. We consider three models of uncertainty:(1) lottery model -in which for each agent, there is a probability distribution over linear preferences, (2) compact indifference model -for each agent, a weak preference order is specified and each linear order compatible with the weak order is equally likely and (3) joint probability model -there is a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 14 publications
0
65
0
Order By: Relevance
“…It would be interesting to know whether it is also complete for LOGSNP. 2 However, LOGSNP-hardness for our problem would also imply LOGSNP-hardness for GRAPH ISOMORPHISM (see Theorem 6.5).…”
Section: Open Problems and Conclusionmentioning
confidence: 88%
See 2 more Smart Citations
“…It would be interesting to know whether it is also complete for LOGSNP. 2 However, LOGSNP-hardness for our problem would also imply LOGSNP-hardness for GRAPH ISOMORPHISM (see Theorem 6.5).…”
Section: Open Problems and Conclusionmentioning
confidence: 88%
“…Aziz et al [2] considered a variant of STABLE MARRIAGE, where each agent has a probability for each ordered pair of potential partners. Assigning a probability of 1 to either (x, y) or (y, x) for each x and y, their variant is closely related to the one of Farczadi et al [23] and is shown to be NP-hard.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Aziz et al [Azi+16] looked at the stable matching problem in settings where there is uncertainty about the preferences of the agents. They considered three different models of uncertainty and primarily studied the complexity of computing the stability probability of a given matching and the question of finding a matching that will have the highest probability of being stable.…”
Section: Related Workmentioning
confidence: 99%
“…They mostly focus on providing algorithms to find such matchings. Aziz et al considered different models to study this problem and mostly focused on the complexity part of the problem [2]. They define stability probability as the probability of a matching being stable.…”
Section: Introductionmentioning
confidence: 99%